Association Between Social Support and Postpartum Depression : A Systematic Review - Leo Medianto Faziqin; Iche Andriany Liberty (Fakultas Kedokteran Universitas Sriwijaya, 2023)
Postpartum depression (PPD) is one of the most common mental disorders occurring during the postpartum period among women. Prevalence of postpartum depression is estimated to be about 10–15% worldwide. Many risk factors are supposed to play a role leading a new mother to maternal postpartum depression which can considerably affect the baby, mother, family and also the society. Some study shown that social support has been effective in helping women cope with PDD and lack of social support increase the risk of PPD. This study aimed to know the association between social support and postpartum depression. This systematic review was conducted using the Preferred Reporting Items for Systematic Review and Meta-analyses (PRISMA) standard. The search using 6 databases SAGE Journals, Pubmed, Science Direct, Springer, Wiley Online Library, and Oxford University Press. The search strategy in each of the databases used keywords such as: (((social support) OR (family support)) AND ((postpartum depression) OR (postnatal depression)) AND (cross sectional)). The process of searching and selecting the studies which yielded a total of 1.814 articles. Only six studies were suitable to answer the study question. Each of the studies were conducted in different areas comprising Iran, China, India, and Korea. The outcome of this study shown that there was association between social support and postpartum depression. Woman with poor social support increase the risk of postpartum depression.